2018
DOI: 10.1002/adma.201807142
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastrong Medium‐Entropy Single‐Phase Alloys Designed via Severe Lattice Distortion

Abstract: thermomechanical processing routes which introduce high densities of dislocations and interfaces into materials. These defect populations introduce long-range stress fields, enabling substantial strengthening of materials. Thus, processing with the aim to introduce high densities of lattice defects into materials is a wellestablished and efficient method to enhance their strength. [12] Yet, when single-phase metallic materials have few defects such as in the recrystallized state and at the beginning of plastic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
139
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 381 publications
(148 citation statements)
references
References 57 publications
9
139
0
Order By: Relevance
“…Previous studies [124][125][126] also demonstrated a substantial contribution of local lattice distortions in CrMnFeCoNi, and actually local lattice distortions are found to enhance solid solution strengthening [19,125,126]. The present paper reveals that the local lattice distortions may also affect the SFEs and thus ductility.…”
Section: A Phase Stability and Sfe Of The Interstitial-free Crmnfeconisupporting
confidence: 72%
See 1 more Smart Citation
“…Previous studies [124][125][126] also demonstrated a substantial contribution of local lattice distortions in CrMnFeCoNi, and actually local lattice distortions are found to enhance solid solution strengthening [19,125,126]. The present paper reveals that the local lattice distortions may also affect the SFEs and thus ductility.…”
Section: A Phase Stability and Sfe Of The Interstitial-free Crmnfeconisupporting
confidence: 72%
“…The equiatomic CrMnFeCoNi alloy, also termed as the Cantor alloy [1], shows a remarkable combination of strength and ductility [2][3][4][5]. Their impressive mechanical properties could be further enhanced by modifying the compositions away from equiatomic CrMnFeCoNi [6][7][8][9][10][11][12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…1 (data points A through E (refs. [22][23][24][25] ) and I 26 ). These HEAs 30 offer high σ y and ε u that are clearly superior to others.…”
mentioning
confidence: 99%
“…One therefore naturally wonders if concentrated alloys can offer (σ y , ε u ) beyond current benchmark ranges [12][13][14][15][16][17][18][19][20][21] . This proposition brings us to the so-called high-entropy alloys (HEAs), also called multi-principal component alloys or complexconcentrated alloys [22][23][24][25][26] . For a systematic introduction to this new paradigm recently emerged in metallurgy, the readers are referred to several review articles [27][28][29][30][31] .…”
mentioning
confidence: 99%
See 1 more Smart Citation